Molecular epidemiological investigation of Brucella melitensis circulating in Mongolia by MLVA16. (February 2017) - Kang, Sung-Il; Her, Moon; Erdenebaataar, Janchivdorj; Vanaabaatar, Batbaatar; Cho, Hyorim; Sung, So-Ra; Lee, Jin Ju; Jung, Suk Chan; Park, Yong Ho; Kim, Ji-Yeon
Highlights: B. melitensis and Rev. 1 were divided into 25 and 4 genotypes, respectively. Mongolian B. melitensis showed a high genetic similarity with Chinese strains. This genotyping revealed circulating of B. melitensis in between animal and human. Abstract: Mongolia has a high incidence of brucellosis in human and animals due to livestock husbandry. To investigate the genetic characteristics of Mongolian B. melitensis, an MLVA (multi-locus variable-number tandem-repeat analysis)-16 assay was performed with 94 B. melitensis isolates. They were identified as B. melitensis biovar (bv.) 1 (67), 3 (10) and Rev. 1 vaccine strains (17) using a classical biotyping and multiplex PCR. In genotyping, three human isolates were grouped at 2 genotypes with sheep isolates, and it implies that B. melitensis are cross-infected between human and livestock. In the parsimony analysis, Mongolian B. melitensis isolates had high genetic similarity with Chinese strains, likely due to the geographical proximity, clustered distinctively as compared with other foreign isolates. B. melitensis Rev. 1 vaccine strains were divided into 4 genotypes with 92% similarity. In the analysis of Rev.1 strains, the risk of mutation of vaccine strain might not be overlooked. Animal quarantines should be strengthened to prevent the spread of Brucella species among adjacent countries.